Prenatal Care for Pregnant Women Living on The Street: Na Integrative Review - Silva, Sara Maria de Oliveira; Gomes, Lara Bianca de Sousa Silva; Freitas, Rosa Caroline Mata Verçosa de; Lima, Josemir de Almeida (JRG Journal of Academic Studies, 2023)
Introduction: The pregnancy process can be considered a social risk factor at the public health level, when integrated with the process of marginalization, poverty and vulnerability, as in pregnant women in street situations. Prenatal care is one of the pillars for promoting health during pregnancy, taking into account all the particularities involved in this process. Thus, it is a matter of great relevance in the context of social vulnerability. General objective: To understand prenatal care for pregnant women living on the streets. Method: This is an integrative literature review, carried out in the period of May 2023, in the databases: Latin American and Caribbean Literature Health Sciences, Database in Nursing and Medical Literature Analysis and Retrieval System Online, through the Virtual Health Library and Scientific Electronic Library Online – Brazil. The Health Sciences Descriptors were used: “Nursing”; "Prenatal"; “Street location”; “Pregnant women” and “Assistance”. Nine studies, published and indexed in the last 10 years (2012-2020), were included. Results: In the initial electronic search, 40 articles were found. With the application of the inclusion and exclusion criteria, 20 articles were chosen for reading the abstracts. After that, 9 articles were selected for full reading. Discussion: Street pregnant women are unprotected in the face of risk conditions, mainly due to lack of care and rights. The nursing professional should instruct the family on the importance of carrying out prenatal care. Conclusion: The integration of health services with public policies aimed at the homeless population is essential to ensure equitable access to prenatal care and to improve maternal and fetal health. Nursing professionals need to be trained to deal with the particularities of this vulnerable group, adapting prenatal care practices to their living conditions.